Cognitive Communication terhadap Persepsi Penonton pada Film Sweet Loan (Studi Kasus pada Akun Instagram @homesweetloanfilm) - Abadi, Totok Wahyu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The purpose of this study is to investigate how audience impressions of the film Home Sweet Loan are influenced by cognitive communication on social media, specifically Instagram. In order to comprehend how narratives, digital interactions, and visual components influence viewers' emotional bonds, this study examines comments on the movie's official Instagram account using a qualitative research approach based on online participant observation. The findings demonstrate how social media content, including pictures, videos, and interactive stories, can affect audience expectations and preferences while forging strong emotional bonds. The study also shows that cognitive communication is crucial for creating favorable opinions about the themes and characters of films in addition to raising audience involvement. This study adds to the body of knowledge on digital marketing, especially when it comes to movie promotion, by providing practitioners with tactical advice on how to maximize audience interaction on social media.